2002
DOI: 10.1074/jbc.m110314200
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2

Abstract: Prostaglandin D 2 (PGD 2 ), a major cyclooxygenase product in a variety of tissues, readily undergoes dehydration to yield the cyclopentenone-type PGs of the J 2 series, such as 15-deoxy-⌬ 12,14 -PGJ 2 (15d-PGJ 2 ), which have been suggested to exert anti-inflammatory effects in vivo. Meanwhile, the mechanism of these effects is not well understood and the natural site and the extent of its production in vivo remain unclear. In the present study, we raised a monoclonal antibody specific to 15d-PGJ 2 and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
119
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(120 citation statements)
references
References 33 publications
1
119
0
Order By: Relevance
“…In atherosclerosis, macrophages play important roles in which oxidized low density lipoprotein accumulates as a major source of oxidized lipid (7). Under inflammatory conditions, macrophages express not only cyclooxygease-2 and 12/15-lipoxygenase, to produce prostaglandins and leukotrienes, respectively (31,32), but also nitric-oxide synthase to generate nitric oxide, another potent oxidative agent (33). In addition, expressions of prostaglandin transporter and 15-hydroxyprostaglandin dehydrogenase, both of which are involved in prostaglandin metabolism to form 15-keto-protstaglandins (34,35), were modulated during lipopolysaccharide-induced fever (36).…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerosis, macrophages play important roles in which oxidized low density lipoprotein accumulates as a major source of oxidized lipid (7). Under inflammatory conditions, macrophages express not only cyclooxygease-2 and 12/15-lipoxygenase, to produce prostaglandins and leukotrienes, respectively (31,32), but also nitric-oxide synthase to generate nitric oxide, another potent oxidative agent (33). In addition, expressions of prostaglandin transporter and 15-hydroxyprostaglandin dehydrogenase, both of which are involved in prostaglandin metabolism to form 15-keto-protstaglandins (34,35), were modulated during lipopolysaccharide-induced fever (36).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, at concentrations in the nanomolar range, A-and J-series PGs induce proliferation (16 -18). One limitation of the studies reported to date with cyclopentenone PGs is that there is marked paucity of evidence that they are formed in vivo (19,20).…”
Section: Docosahexaenoic Acid (C22:63 Dha)mentioning
confidence: 99%
“…cyPG have been detected in situations associated with an increase in cyclooxygenase-2 expression and PG production, such as acute and chronic inflammatory conditions (2)(3)(4). In addition, generation of cyPG has been reported in several experimental models, such as activated macrophages and mesangial cells (3,5). cyPG have received considerable attention during the past decade due to their action as antiproliferative agents and inducers of apoptosis in a variety of normal and cancer cell types (6,7).…”
mentioning
confidence: 99%
“…Dehydration of PGD 2 gives rise to PGJ 2 and 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), whereas PGE 2 is converted into PGA 2 (1). cyPG have been detected in situations associated with an increase in cyclooxygenase-2 expression and PG production, such as acute and chronic inflammatory conditions (2)(3)(4). In addition, generation of cyPG has been reported in several experimental models, such as activated macrophages and mesangial cells (3,5).…”
mentioning
confidence: 99%